2014
DOI: 10.1007/s12114-014-9185-y
|View full text |Cite
|
Sign up to set email alerts
|

Assets and African Americans: Attempting to Capitalize on Hopes for Children through College Savings Accounts

Abstract: Although some racial inequalities have lessened in the half-century since the passage of the first major civil rights legislation, the racial wealth gap remains and in recent years seems to be widening. Households with children are the least likely to be asset secure or have sufficient resources to enable investment in opportunities for mobility. Viewing inequality from this perspective indicates that what households are able to save and invest for the future might have a more lasting impact on the life chance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…These findings suggest that low-income families could have benefited from consumer information that enabled making healthier nutritional choices that could have maximized the health impact of increased expenditures on food. An intervention that targeted low-income black and white parents to start a college education fund for their child in Head Start also illustrates the need to empower consumers with information [119]. In this project a parent’s deposit of $25 would provide $1000 in the child’s account, and any additional deposits by the parent would be matched dollar for dollar.…”
Section: Strategy Number 3: Raising Awareness Of Inequities and Bumentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that low-income families could have benefited from consumer information that enabled making healthier nutritional choices that could have maximized the health impact of increased expenditures on food. An intervention that targeted low-income black and white parents to start a college education fund for their child in Head Start also illustrates the need to empower consumers with information [119]. In this project a parent’s deposit of $25 would provide $1000 in the child’s account, and any additional deposits by the parent would be matched dollar for dollar.…”
Section: Strategy Number 3: Raising Awareness Of Inequities and Bumentioning
confidence: 99%
“…However, only 62% of the black parents and 67% of the white parents enrolled in the program. An evaluation revealed that these parents had low levels of financial literacy, a history of negative experiences with financial institutions and more severe household financial constraints than was recognized by the designers of the intervention [119]. Thus, a successful intervention requires adequate awareness and empowerment on the part of the targeted group.…”
Section: Strategy Number 3: Raising Awareness Of Inequities and Bumentioning
confidence: 99%
“…Other studies have shown that people from low-SEP groups are unable to take advantage of interventions that directly benefit them because of other daily life challenges. 41 Limitations Not all instances of computer issues may have been reported, leading us to underestimate barriers. Our sample may not be representative of other low-SEP groups in Boston or the United States.…”
Section: Perceived Barriersmentioning
confidence: 99%
“…The goal of this initial phase is to increase the client's trust in the program and the worker, and to begin the process of establishing a sense of engagement in the FCAB process. Building trust is essential; previous research on asset building programs has demonstrated that participating with an agency that is trusted throughout the community is key for the process of recruiting participants (Shanks, Nicoll, & Johnson, 2014). Similarly, key staff members who are able to foster a sense of trust and build rapport with clients can be extraordinarily helpful in linking clients to FCAB programs and policies (Scanlon & Wittman, 2010).…”
Section: Rapport-building and Engagementmentioning
confidence: 99%